A Survey on Handwritten Character Recognition Techniques for Tamil Language - Lincy R, Babitha; R, Gayathri (International Journal of Engineering and Technology, 2018)
Nowadays the most remarkable and fascinating success of optical character recognition system for the printed Tamil text leads to extremely interesting challenges in the part of handwritten identification tool for Tamil text because of its various research solicitations. Recognition of Tamil character has been broadly studied in the previous year by the academic laboratories and research companies. Presently the researchers have taken their attention towards various recognition methodologies for Tamil handwritten character recognition due to its open challenges. The aim of this survey is to exchange the different aspects of Tamil OCR and resolving the issues of Tamil handwritten OCR by conferring performance of the various techniques.Â Â